ANALISIS PERAN ACCOUNT RECEIVEABLE PADA ACCOUNTING DEPARTMENT THE SAHID RICH JOGJA HOTEL - , RETNO YUNIA NUGRAHIKA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tourism in Indonesia show progress and rapid growth. The development of the tourism sector in a country will attract other supporting sectors in areas such as accommodation. Similarly the city of Yogyakarta which had always been known as the City Tour. Due to as a tourist destination that is certainly supporting tourism products join other experiencing growth. Yogyakarta city has hotels ranging from budget to five-star types. And that the business has a very promised profit, the profit derived from the revenue or income. In the set there should be revenue department that manages the system so that all runs smoothly and goes well that will produce maximum profit as well. The section that is Accounts Receivable which is part of the Accounting Department. The purpose of this final assignment for know the role of an Accounts Receivable toward acquirement of Income The Sahid Rich Jogja Hotel. Technique of analyzing data used include descriptive qualitative . Descriptive qualitative data Technique analyze are used to provide an overview of the actual variable. From the analysis it can be seen the role of A / R Accounts Receivable and workflow from beginning to end. From the analysis it can be seen that the role of Accounts Receivable for The Sahid Rich Jogja Hotel is very important. The role of Account Receivable The Sahid Rich Jogja Hotel in surveillance has been going quite well and in accordance with existing procedures. Accounts Receivable has been carrying out a good control of the transaction processing companies, especially in terms of revenue or income, so that corporate goals can be achieved in increasing income.